Interpreting The State's Right to Control In the provisions of Article 33 Paragraph (3), The Constitution of 1945 Republic of Indonesia - Suparto Suparto (UIR Press, 2020)
Article 33 paragraph (3) of The Constitution Republic of Indonesia in 1945 stipulates that